Pengaruh Nilai Tambah dan Efisiensi Pemasaran Sagu Terhadap Pendapatan Pengolah Sagu di Kabupaten Konawe Provinsi Sulawesi Tenggara Indonesia - Surni, Surni; Limi, Muhammad Aswar; Zani, Munirwan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
This research was conducted to analyze the effect of added value and marketing efficiency on sago processing income. This research was conducted in Konawe District and sampling using snowball techniques as many as 26 sago processors. Data analysis uses multiple regression. The results of the analysis note that 45.90% of the variation in income variables can be explained by value-added and processor share variables while 54.10% is explained by other variables outside the model where the added value and marketing efficiency variables have a significant effect. on sago processing income.